A general assessment of the impacts of variable power generation in an integrated power grid - Saeed, Sayed Farhad (Kansas State University, 2021)
With the increasing concerns for the environment, there is a growing demand to replace conventional thermal generators with renewable energy resources. Large-scale penetration of renewable resources such as wind and solar imposes significant challenges on the stability and reliability of existing power systems. Due to their variable and uncertain nature, they have fluctuating generation outputs at multiple timescales. System operators face difficulties determining the appropriate scheduling for the generating units and providing sufficient reserve requirements to balance load and generation. Therefore, the optimal scheduling and dispatching of the generating units in an integrated power system necessitate efficient mitigation approaches. This report is a general assessment of the impacts of renewable energy sources, like wind and solar, on an existing power grid. It also describes the deterministic and stochastic unit commitment methods currently used to economic dispatch and deals with wind and solar fluctuations. For a better illustration of the variability and uncertainty impacts of variable generation, an IEEE RTS-96 is solved with an energy scheduling simulation tool (FESTIV) to provide deterministic results.
Keywords: Impacts of variable power generation; Integrated power grid